2021
DOI: 10.18820/2519593x/pie.v39.i2.17
|View full text |Cite
|
Sign up to set email alerts
|

What are teachers' beliefs, values and attitudes towards the inclusion of learners who experience barriers to learning in South African primary schools?

Abstract: This study examined teachers' attitudes towards the inclusion of learners who experience barriers to learning in their classrooms.The study implemented the quantitative descriptive design. Sixtythree Foundation Phase (grades 1-3) teachers were recruited through the convenient sampling strategy from the Capricorn District in Limpopo Province in South Africa. Data were collected through a closed-ended questionnaire adapted from the Teaching for All (Department of Basic Education, 2019) student support materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Similarly, Mamabolo et al (2021) found that teachers held disbelief that learners with learning barriers would improve their social skills in mainstream schools. Acquiring knowledge about teachers' attitudes plays a crucial role in entrusting teachers with the diverse needs of learners (Mamabolo et al, 2021).…”
Section: Screening Identification Assessment and Support Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Mamabolo et al (2021) found that teachers held disbelief that learners with learning barriers would improve their social skills in mainstream schools. Acquiring knowledge about teachers' attitudes plays a crucial role in entrusting teachers with the diverse needs of learners (Mamabolo et al, 2021).…”
Section: Screening Identification Assessment and Support Policymentioning
confidence: 99%
“…Similarly, Mamabolo et al (2021) found that teachers held disbelief that learners with learning barriers would improve their social skills in mainstream schools. Acquiring knowledge about teachers' attitudes plays a crucial role in entrusting teachers with the diverse needs of learners (Mamabolo et al, 2021). These findings were confirmed by a study conducted in South Korea, where teachers' attitudes were seen to play a significant role when implementing inclusive education (Song, Sharma & Choi, 2019).…”
Section: Screening Identification Assessment and Support Policymentioning
confidence: 99%